CROSS-CULTURAL FACTORS THAT INFLUENCE ADJUSTMENTS OF FOREIGN CARE WORKERS IN JAPAN: TOWARDS A THREE-LAYERED STRUCTURAL MODEL - Hatanaka, Kaori; Tanaka, Tomoko (LIFE: International Journal of Health and Life-Sciences, 2016)
In Japan, foreign care workers have been increasing, thus cross-cultural adjustment has become an important issue. In this study, we examined factors that influence (1) psychological, (2) sociocultural, and (3) self-realization adjustments of foreign care workers. Participants were from Indonesia (n=70) and the Philippines (n=88) that work at medical (n=32) and elder care facilities (n=72) in Japan. Participants completed questionnaires that measured the three adjustments. A multilevel model analysis was used to examine the relationship between the three adjustment variables. Seven factors were identified. In assessing a three layered structural model, it was found that cross-cultural adjustment is first influenced by psychological factors that influence sociocultural factors of the middle layer, and self-realization factor affected by sociocultural factors. The original three-layer model that simply progress from psychological to self-realization was differ and it was modified. The key factor of cross cultural adjustment of affinity relation with Japanese was indicated.